Producción de forraje Hidropónico de cebada (Hordeum vulgare L.) y Maíz ( Zea mays L.) con la aplicación de tres hormonas. - Silva Esparza, Dayana de los Angeles (2017)
This following project was realized at the Experimental Station “La Argelia” with the main goal to test three hormones in barley and corn in a Forage Hydroponic Green System (HGS) with the purpose of offering alternatives in forage production through of the hydroponic crops. For this study was used the design completely random with a factorial arrangement 2x4 with the results was analyzed by ADEVA and the Tukey test 5% to determine statistical significances between treatments and two forages species as: barley (A1) and corn (A2). The hormones used in the treatments were: RAIZAL® 400 (T1), CYTOKIN® (T2), NEWGIBB® 10 SP (T3) and witness (T0). It was evaluating at 5 and 18 days after germination the following variables: plant height, biomass production, (kg) forage nutritive value; protein, ashes, cruder fiber, and grease. The best results after germination were obtaining in the barley with the application of CYTOKIN® at 18 days shows the major values in plant height and forage weight. In the hydroponic corn the best treatment in the plant height was with the application of NEWGIBB® 10 SP and in the biomass production was with the treatment with CYTOKIN®. About plant height at the 18 days after germination the barley shows showed with the application of CYTOKIN® (21,30 cm) and the corn with the same treatment (7,20 cm) meanwhile with the NEWGIBB® 10 SP (12,80cm). The best performance in the biomass production was found in the barley treatment with CYTOKIN® (1,08 Kg) with the same treatment in the corn (1,10 Kg). In the protein the results variety with the relation at the forage specie. The barley by application of CYTOKIN® shows the highest value (16,76%) meanwhile that the corn with the same hormone was (13,14%). The percentage of fiber was highest in the barley with CYTOKIN® (19,45%), meanwhile the corn showed the lowest values with CYTOKIN® (13,14%), but in less percentage with NEWGIBB® 10 SP (10,36%). As for fat, the highest percentage was found in the witnesses in both barley (2.83%) and maize (4.08%). Finally, the nutritional quality of the hydroponic crops of the forage species under study showed that barley reported the best results in the bromatological analyzes (Protein, crude fiber, ash, fat); And lower values ​​in maize, which should be considered the hydroponic cultivation of barley in the choice and production of crops or forage species that improve the nutritional quality contributing to animal feed. Key words: Hydroponic forage, corn, barley.